Methodical approach of building an integrated assessment of the effectiveness of involving alternative energy sources - Sailaubekov, N.T.; Shaihutdinova А.К.; Baitanaeva B.А. (Journal of Economic Research & Business Administration, 2016)
In the work shows methodical approach of building an integrated as-sessment of the effectiveness of involving alternative energy sources. As-sumed that this evaluation will be prepared on the basis of the six blocks indicators like are financial and economic, out energy, social, budget, eco-logical and energetically significant and their weight. Estimates for each block can be obtained on the basis of standard matrices which can be constructed by using method of dynamic normative. Integral assessment can be used in selecting the most effective type of energy carrier on the basis of alternative energy source.